Cell jamming: Collective invasion of mesenchymal tumor cells imposed by tissue confinement - Haeger, Anna; Krause, Marina; Wolf, Katarina; Friedl, Peter (Biochimica et biophysica acta, 2014)
Cancer invasion is a multi-step process which coordinates interactions between tumor cells with mechanotransduction towards the surrounding matrix, resulting in distinct cancer invasion strategies. Defined by context, mesenchymal tumors, including melanoma and fibrosarcoma, develop either single-cell or collective invasion modes, however, the mechanical and molecular programs underlying such plasticity of mesenchymal invasion programs remain unclear. To test how tissue anatomy determines invasion mode, spheroids of MV3 melanoma and HT1080 fibrosarcoma cells were embedded into 3D collagen matrices of varying density and stiffness and analyzed for migration type and efficacy with matrix metalloproteinase (MMP)-dependent collagen degradation enabled or pharmacologically inhibited. With increasing collagen density and dependent on proteolytic collagen breakdown and track clearance, but independent of matrix stiffness, cells switched from single-cell to collective invasion modes. Conversion to collective invasion included gain of cell-to-cell junctions, supracellular polarization and joint guidance along migration tracks. The density of the extracellulair matrix (ECM) determines the invasion mode of mesenchymal tumor cells. Whereas fibrillar, high porosity ECM enables single-cell dissemination, dense matrix induces cell–cell interaction, leader–follower cell behavior and collective migration as an obligate protease-dependent process. These findings establish plasticity of cancer invasion programs in response to ECM porosity and confinement, thereby recapitulating invasion patterns of mesenchymal tumors in vivo. The conversion to collective invasion with increasing ECM confinement supports the concept of cell jamming as a guiding principle for melanoma and fibrosarcoma cells into dense tissue. This article is part of a Special Issue entitled Matrix-mediated cell behaviour and properties. •Collective invasion of mesenchymal tumor cells results from confinement with increasing ECM density.•ECM-induced collective invasion requires track clearance by leader cells.•Collective cooperation includes cell–cell junctions, joint polarity & aligned paths.•Melanoma and fibrosarcoma cells show a homologous plasticity response.•Cell jamming underlies confinement-induced collective migration in 3D ECM.